Finance Account Receivable pada PT Dom Pizza Indonesia - Yeni Rahmawati; Karmudiandri, Arwina; Firnanti, Friska; Sutrisno, Paulina (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The objective of the MBKM program is to increase the competency value of graduates, both in soft skills and hard skills, to obtain the means to implement the knowledge gained from lectures into a real work environment, and to increase knowledge about the scope and work culture of companies, especially companies in the Food and Beverage sector. MBKM participants in the Account Receivable subdivision are given a number of tasks that are repeated daily and weekly, including recapitulating voucher payments from all stores and billing to PT. Sodexo Motivation Solutions Indonesia, makes journal data and imports the data into SAP, makes account data from FEM domino's and reconciles payments for e-wallets, makes Invoices and Reimbursement according to requests, and makes journalism for CIMB NIAGA Bank in SAP. The conclusion of the MBKM program activities is that the activities run quite effectively and efficiently, participants get the opportunity to gain knowledge and experience from routine and non-routine activities as well as from innovation projects that have been completed. Innovation projects that have been made by participants with approval from superiors, these innovation projects will later be continued by the next participant. In addition, MBKM participants also gain knowledge regarding journals related to accounts receivable, payment reconciliation, invoices, expertise in SAP operations and other soft skills that are very useful for the participants' future careers.